Verbal and nonverbal language in EFL classrooms - Dantas, Lílian Maria; Tavares, Roseanne Rocha (Revista Leitura, 2019)
The main objective of this paper is to show some results from a research that focused on the influence of nonverbal language (together with verbal) in EFL classroom interaction. The methodological approach chosen to execute it had an ethnographic focus, based on Erickson's (1996) ethnographic micro-analysis of interaction. The focus of our investigation turned out to be the smile. The three types of smile noticed contributed to lower the affective filter, increase interaction and consequently improve students' learning. DOI: 10.28998/0103-6858.2007v1n39p15-34